Modified maximum power point tracking based-on ripple correlation control application for single-phase VSI grid-connected PV systems - Boonmee C. (2014)
In this paper, the modified maximum power point tracking (MPPT) based-on the ripple correlation control technique application for single-phase voltage source inverter (VSI) grid-connected photovoltaic (PV) system is proposed. The algorithm has been developed by using the mean function instead of the 1 st order highpass filters (HPFs) and lowpass filters (LPFs) to control the maximum power transferring from a PV string to the utility grid through the single-phase VSI. This method can generate the sinusoidal current with the unity power factor. Additionally, the proposed method is a simple algorithm which causes higher accuracy and reliability for correction of the maximum power point when compared with the used of HPFs and LPFs technique subjected on rapidly shading irradiance. It can reduce a PV voltage harmonic filter in the dc-link voltage controller. Simulation results of the VSI grid-connected PV system with two situations of full and half PV string shading control are presented to confirm the effectiveness of the modified MPPT process. © 2013 IEEE.